LEARNING INNOVATION: APPLICATION OF DISCOVERY LEARNING-BASED WORKSHEETS TO SHARPEN STUDENTS’ COLLABORATION SKILLS ON HYDROELECTRIC POWER PLANTS - Winedar, Ihza Rizky; Unayah, Habibatul; Rasyid, Muhammad; Jumadi, Jumadi; Nurohman, Sabar (JURNAL EDUSCIENCE, 2025)
Purpose—In the 21st century, where education emphasizes the development of holistic competencies, collaboration skills have become an important aspect of preparing students to face the complex demands of the real-world environment. This study aims to analyze the effect of discovery learning on improving students' collaboration skills in studying alternative energy sources, mainly hydropower.Methodology – This research employed a quasi-experimental design featuring a one-group pretest-posttest method, with 35 students at SMP IT Ibnu Abbas serving as participants. The sample was chosen using a random sampling approach, ensuring that every individual in the population had an equal chance of being selected. Information regarding students' collaboration skills was gathered through self-assessment using a questionnaire. The collected data were analyzed using descriptive statistical methods to provide an overview of the results and inferential statistics to test hypotheses and reach more detailed conclusions.Findings—The results indicate a notable enhancement in students' collaboration abilities following the adoption of the discovery learning model, with the mean score increasing from 28.49 on the pre-test to 36.34 on the post-test. A paired sample t-test validated this change, yielding a significance level of 0.000. The N-Gain assessment also demonstrated a medium effectiveness level with an average score of 0.3255. The discovery learning model successfully improved collaboration skills through active exploration, discussion, and problem-solving, underscoring its potential to promote 21st-century competencies among students.Significance – In addition, this approach provides a reference for implementing strategic steps to help high school students improve their collaborative skills, fostering essential non-academic achievements like teamwork and problem-solving for their future success.